Habib Rishiq Shihab Hate Speaking On Youtube social Media: Forensic Linguistic Analysis - Alfian Mahajir Alfian; Tadjuddin Maknun; Kamsinah Kamsinah; Firman Saleh (La Ogi : English Language Journal, 2022)
This study aims to explain the forms of speech acts that contain Habib Rishiq Shihab's hate speech on YouTube social media. The data in this study are Habib Rishiq Shihab's story uploaded on YouTube social media which contains hate speech. The source of the data in this study is a document in the form of a video uploaded on YouTube social media related to Habib Rishiq Shihab's speech which contains hate speech.The method used in this study is a qualitative descriptive method, data collection techniques look-see and note. Data were analyzed usingThe data analysis technique used is qualitative content analysis.The results of this study indicate that:Habib Rishiq Shihab's speech on YouTube contains declarative and interrogative speech acts. The form of illocutionary speech acts uses declarative and directive locutions. The form of perlocutionary speech acts is in the form of a deliberate effect by influencing the interlocutor. Such speech is considered as a form of provocative/incitement that can cause feelings of hatred or hostility towards certain individuals and/or community groups based on ethnicity, religion, race, and inter-group (SARA) so that they can be categorized as having committed an unlawful act as regulated in the formulation of article 45A paragraph (2) UU ITE and Article 160 of the Criminal Code.